Immigration Enforcement and Childhood Poverty in the United States - Catalina Amuedo-Dorantes; Esther Arenas-Arroyo; Almudena Sevilla (Institute for the Study of Labor (IZA), 2016)
Over the past two decades immigration enforcement has grown exponentially in the United States. We exploit the geographical and temporal variation in a novel index of the intensity of immigration enforcement between 2005 and 2011 to show how the average yearly increase in interior immigration enforcement over that time period raised the likelihood of living in poverty of households with U.S. citizen children by 4 percent. The effect is robust to a number of identification tests accounting for the potential endogeneity of enforcement policies, and is primarily driven by police-based immigration enforcement measures adopted at the local level such as 287(g) agreements.
Keywords: I38; J15; K37; 330; immigration enforcement; poverty; U.S. citizen children; unauthorized parents